Idiopathic Intracranial Hypertension Presenting as Auditory Neuropathy Hearing Disorder in a Child. (3rd July 2019) - Tobia, Amjad; Khayr, Ranin; Shpak, Talma; Peleg, Caroline; Genizi, Jacob; Khnifes, Riyad; Borissovsky, Nina; Luntz, Michal
Abstract : Otologic manifestations are known to occur in patients with idiopathic intracranial hypertension (IIH), but the occurrence of sensorineural hearing loss, especially in pediatric populations, has been addressed in only a few reports. Here, we describe a pediatric patient who presented with IIH and severe bilateral hearing loss. The patient's hearing loss was diagnosed as a form of auditory neuropathy (AN) and resolved after prompt treatment of the increased intracranial pressure. This case points to a possible association between IIH and AN and suggests that IIH may potentially be a reversible cause of AN spectrum disorder. Laryngoscope, 129:E407–E411, 2019